Determination of bending angle of light deflection subject to possible weak and strong quantum gravity effects - Xu, Chenmei; Yang, Yisong (International journal of modern physics. A, Particles and fields, gravitation, cosmology, 2020)
Explicit expressions for the bending angle of light deflection arising from phenomenologically deformed black hole metrics, subject to possible weak and strong quantum gravity effects, respectively, are obtained, by a highly effective method. The accuracy and effectiveness of these expressions are then illustrated by numerically solving the differential equation governing the deflection angle directly in the weak quantum-gravity effect situation.